Concerns about weight and mental health among adolescent gymnasts: a pilot study - Little, C.; Howell, D.; Armento, A.; McCarthy, A.; Sweeney, E. (Science of Gymnastics Journal, 2023)
Weight concerns can have an effect on gymnasts` quality of life. We examined the association between concerns about weight with self-reported anxiety levels and other psychosocial and menstrual health characteristics among child and adolescent gymnasts. Gymnasts between 8 and 18 years old completed an online questionnaire distributed by their gymnastics clubs. They also completed the Generalized Anxiety Disorder (GAD-7) questionnaire. Of the 73 gymnasts who completed the questionnaire, 15% reported worrying about their weight; they were significantly older and reported higher GAD-7 scores than those who did not worry about their weight. After adjusting for the independent effect of age, worrying about weight was no longer significantly associated with GAD-7 scores (adjusted odds ratio= 1.13, 95% CI=0.98, 1.30, p=0.10), beliefs about their body size (adjusted odds ratio=6.48, 95% CI=0.84, 50.1; p=0.07), or menarche (adjusted odds ratio=0.40, 95% CI=0.04, 4.14, p=0.44). We found an association between age, anxiety, and weight concerns in child and adolescent gymnasts. Healthcare providers should screen for weight concerns and increased anxiety in older gymnasts.